The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3382/ps/peu018
|View full text |Cite
|
Sign up to set email alerts
|

Administration of a Salmonella Enteritidis ΔhilAssrAfliG strain by coarse spray to newly hatched broilers reduces colonization and shedding of a Salmonella Enteritidis challenge strain

Abstract: Consumption of contaminated poultry meat is still an important cause of Salmonella infections in humans. Colonization inhibition (CI) occurs when a live Salmonella strain is administered to chickens and subsequently protects against challenge with another Salmonella strain belonging to the same serotype. A Salmonella Enteritidis hilAssrAfliG deletion mutant has previously been proven to reduce colonization and shedding of a wild-type Salmonella Enteritidis strain in newly hatched broilers after experimental in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
14
1
Order By: Relevance
“…Both Salmonella counts and the inflammatory response confirmed that aerosol vaccination induced a greater systemic immune response. However, unlike in previous studies [ 10 12 ], the aerosol vaccination was less protective in the cecum than the oral vaccination. It is likely that multiple sites including the digestive tract, respiratory tract or conjunctiva are stimulated during aerosol vaccination which results in a systemic immune response.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Both Salmonella counts and the inflammatory response confirmed that aerosol vaccination induced a greater systemic immune response. However, unlike in previous studies [ 10 12 ], the aerosol vaccination was less protective in the cecum than the oral vaccination. It is likely that multiple sites including the digestive tract, respiratory tract or conjunctiva are stimulated during aerosol vaccination which results in a systemic immune response.…”
Section: Discussioncontrasting
confidence: 91%
“…Aerosol vaccination is an efficient alternative to oral vaccination [ 10 12 ]. Another alternative increasing the vaccine’s potential is the administration of a live Salmonella vaccine together with probiotics or competitive exclusion products [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non- inoculated, susceptible sentinel birds mirror the animals naturally infected by the oral uptake of resistant bacteria from their surrounding environment after they were shed by the seeder birds. In the course of this, a variety of different ratios is known and a ratio of 1:5 seeder- to sentinel birds is more often described for the inoculation with Enterobacteriaceae (Methner et al, 2011; de Cort et al, 2015; Kilroy et al, 2015). Using this relation led to a complete colonization of all birds within our group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with aerosol vaccination (ATTERBURY et al, 2010;DE CORT et al, 2015) showed that multiple sites including the digestive tract, respiratory tract, and conjunctiva are stimulated during aerosol vaccination, resulting in a systemic immune response, while oral administration of the vaccine stimulates a localized immune response in the intestinal tract. De Cort et al (2015) also suggested that oral immunization with live attenuated vaccine induces a mechanism that inhibits colonization and protects the bird from subsequent challenge, since young chickens are still immature and vaccination is not effective protection against Salmonella infection during the first days of life.…”
Section: Discussionmentioning
confidence: 99%